1997
DOI: 10.1074/jbc.272.48.30009
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a cDNA Coding forl-Galactono-γ-Lactone Dehydrogenase, an Enzyme involved in the Biosynthesis of Ascorbic Acid in Plants

Abstract: L-Galactono-␥-lactone dehydrogenase (EC 1.3.2.3; GLDase), an enzyme that catalyzes the final step in the biosynthesis of L-ascorbic acid was purified 1693-fold from a mitochondrial extract of cauliflower (Brassica oleracea, var. botrytis) to apparent homogeneity with an overall yield of 1.1%. The purification procedure consisted of anion exchange, hydrophobic interaction, gel filtration, and fast protein liquid chromatography. The enzyme had a molecular mass of 56 kDa estimated by gel filtration chromatography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
127
0
8

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 141 publications
(141 citation statements)
references
References 46 publications
6
127
0
8
Order By: Relevance
“…Previous data from other authors have indicated that the protein responsible for l-GLD activity is located at the mitochondrial fraction of plant cells (Ô ba et al, 1994Mutsuda et al, 1995;Østergaard et al, 1997). However, its exact localization has not as yet been investigated.…”
Section: Discussionmentioning
confidence: 87%
“…Previous data from other authors have indicated that the protein responsible for l-GLD activity is located at the mitochondrial fraction of plant cells (Ô ba et al, 1994Mutsuda et al, 1995;Østergaard et al, 1997). However, its exact localization has not as yet been investigated.…”
Section: Discussionmentioning
confidence: 87%
“…Proteins with known functions include l-gulonolactone oxidase of rat (GULOX_RAT; Koshizaka et al, 1988), l-galactono-1,4-lactone dehydrogenase of Brassica oleracea (DEHYD_BRAOL; Ostergaard et al, 1997), alkyldihydroxyacetonephosphate synthase of human (ADAS_HUMAN; de Vet et al, 1997), berberine-bridge-forming enzyme of Eschscholzia californica (BBE_ECALI; Dittrich and Kutchan, 1991), glycolate oxidase subunit of Helicobacter pylori (GLCOX_HPY; Tomb et al, 1997), and d-lactate dehydrogenase of Archaeoglobus fulgidus (DLDEHYD_AF; Klenk et al, 1997). Mushegian and Koonin (1995) initially proposed that the domain illustrated in Figure 5B is conserved among a broad spectrum of oxidoreductases requiring FAD as a prosthetic group.…”
Section: Molecular Characterization Of Dwf1 Allelesmentioning
confidence: 99%
“…The reaction was stopped by adding aliquots to an equal volume of 6% metaphosphoric acid/2.5 mm DTT/1 mm EDTA, containing 2.5 mg L Ϫ1 d-isoascorbic acid as an internal standard. After the samples were centrifuged at 20,000g for 2 min, the l-AA content was analyzed by HPCE, essentially as previously described (Davey et al, 1997). For localization of l-AA biosynthetic activities, cell extracts were centrifuged for 15 min at 10,000g.…”
Section: High-performance Capillary Electrophoresis (Hpce) Analysis Omentioning
confidence: 99%
“…The final oxidation of l-GL to l-AA is catalyzed by the relatively well-characterized enzyme l-galactono-1,4-lactone dehydrogenase (GLDH). GLDH has been purified from the mitochondrial fractions of several sources (Mapson and Breslow, 1958;Ô ba et al, 1994Mutsuda et al, 1995;Østergaard et al, 1997;Imai et al, 1998), and has recently been cloned from cauliflower (Østergaard et al, 1997) and from sweet potato (Imai et al, 1998). The substrate l-GL has also been reported to be a natural component of plant 1 extracts (Østergaard et al, 1997;Wheeler et al, 1998).…”
mentioning
confidence: 99%